The challenges for antarctic governance in the early twenty-first century - McGee, J; Liu, N (Australian Journal of Maritime & Ocean Affairs, 2019)
The Antarctic Treaty has effectively managed this tension by demilitarising the Antarctic continent and directing all human presence on the continent towards peaceful use and scientific research.